2017
DOI: 10.1186/s12893-017-0236-8
|View full text |Cite
|
Sign up to set email alerts
|

Case report: preoperatively diagnosed perforated Meckel’s diverticulum containing gastric and pancreatic-type mucosa

Abstract: BackgroundMeckel’s diverticulum is the most common congenital malformation of the gastrointestinal tract, and it represents a persistent remnant of the omphalomesenteric duct. Although it mostly remains silent, its infrequent occurrence is mirrored by the paucity of large series of data on it in the literature. Hemorrhage, obstruction and inflammation are most common complications of Meckel’s diverticulum. Perforation of Meckel’s diverticulum is considered very rare.Case presentationWe present the case of a 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
(24 reference statements)
0
12
0
3
Order By: Relevance
“…Perforation, however, can be life-threatening and the diagnosis can be delayed or missed considering the overlap of clinical symptoms with other causes of acute abdomen, in addition to the often-non-specific findings on imagining. As previously reported, CT scans and ultrasound are not diagnostic as they are unable to differentiate between a diverticulum and a loop of bowel [ 5 ]. Therefore, establishing the correct pre-operative diagnosis can be challenging due to the non-specific symptoms Meckel’s diverticulum can present with.…”
Section: Discussionmentioning
confidence: 99%
“…Perforation, however, can be life-threatening and the diagnosis can be delayed or missed considering the overlap of clinical symptoms with other causes of acute abdomen, in addition to the often-non-specific findings on imagining. As previously reported, CT scans and ultrasound are not diagnostic as they are unable to differentiate between a diverticulum and a loop of bowel [ 5 ]. Therefore, establishing the correct pre-operative diagnosis can be challenging due to the non-specific symptoms Meckel’s diverticulum can present with.…”
Section: Discussionmentioning
confidence: 99%
“…Hildamus tarafından 1598 yılında tanımlanmıştır. Alman anatomist Johann Friedrich Meckel 1809'da yayınlandığı makalede embriyolojik ve patolojik özelliklerini tarif etmiştir [22]. GIS'in en sık görülen konjenital anomalisidir.…”
Section: Meckel Divertikülü (Md) Ilk Kez Fadriciusunclassified
“…Literatürde olguların %2'sinde semptom görülmektedir. Tüm yaşam boyu komplikasyon oranı yaklaşık %4'tür [22,23]. En sık rastlanan semptomlar; kanama, takiben bağırsak tıkanıklığı, divertikülit, intussusepsiyon, neoplazi ve perforasyondur [22,24].…”
Section: Meckel Divertikülü (Md) Ilk Kez Fadriciusunclassified
See 1 more Smart Citation
“…reported that there were no cases in which Meckel's diverticulum could be diagnosed preoperatively as a cause of bowel obstruction without a history of laparotomy . Abizeid and Aref, however, reported a case of perforated Meckel's diverticulum preoperatively diagnosed on CT . The preoperative diagnosis rate of Meckel's diverticulum will improve with further advances in imaging modalities.…”
mentioning
confidence: 99%